Improving Reading Skill through Story Grammar Strategy for the Eight Grade Students at SMP Muhammadiyah 4 Giri - Puspitasari, Dian Lusianti (Jetlal, 2017)
This study is to know the use of Story Grammar strategy to improve reading skill at eight grade students of SMP Muhammadiyah 4 Giri. The design of the study is classroom action research. The researcher played two roles in this research; as a teacher and a researcher. During implementing the strategy in the classroom, the researcher was accompanied by teacher partner. This research was conducted in one cycle, which was divided into four main activities; planning, acting, observing, and reflecting. The reflection was based on the findings during the observation and compared with criteria of success including: (1) students’ average score is 60 (passing grade for English lesson), and (2) students can participate actively in the class. The research findings showed that this strategy was effective to teach reading comprehension at eight grade students of SMP Muhammadiyah 4 Giri. It was indicated on the students’ average score of post test. The students’ average score in the pretest was 37. After applying Story Grammar strategy the score improved in the post test. The students’ average score in the post was 70,28. The improvement was also shown in the students’ performances in the class. In the first meeting, some students could not join the activity in the classroom well. Day by day, students performed increased during teaching learning process until the fourth meeting. They showed their motivation and participation well. Finally, it can be concluded that Story Grammar strategy could improve students’ reading comprehension skill. The researcher suggests for English teachers especially in teaching speaking to use Story Grammar strategy. Then for the future researchers can apply such technique more deliberately, so the reading comprehension problems could be solved well.